FACTORS AFFECTING IMPLEMENTATION OF EVIDENCE BASED PRACTICE AMONG PHYSIOTHERAPISTS IN MOI TEACHING REFFERAL HOSPITAL KENYA (International Journal of Physiotherapy, 2016)
Background: The application of the concept of Evidenced Based Practice into clinical decision-making and practicehas outstanding benefits both to clinicians and the patient. However, the utilization of this concept has not been copiously utilized in most health facilities by the physiotherapists in Kenya. Therefore, the objectives for this study was to determine the level of awareness of evidence based practice among Physiotherapist, establish the availability of resource for Evidence Based Practice and to assess the challenges encountered by physiotherapist in engaging in evidence based practice at Moi Teaching and Referral Hospital.Methods: All physiotherapists working in Moi Teaching and Referral Hospital (42) took part in a cross-sectional descriptive survey. Questionnaires were used for data collection and analyzed by SPSS version 22.Results: there was high level of awareness on Evidence Based Practice (95 %) and confidence in EBP (72.5 %). However, lack of information resources, poor skills to implement EBP, poor organization support 90%, insufficient authority to induct change in the practice setting 85%, inadequate facilities 74% and lack of time were identified as the major challenges in implementation of EBPConclusion: Strategies should be developed to provide PTs with EBP resources, such as access to databases or links to guidelines, and continuous education regarding specific topics. Professional organizations and Associations should aim at changing the current practice to ensure full utilization of EBP.